2006
DOI: 10.1126/science.1130880
|View full text |Cite
|
Sign up to set email alerts
|

Out of the Tropics: Evolutionary Dynamics of the Latitudinal Diversity Gradient

Abstract: The evolutionary dynamics underlying the latitudinal gradient in biodiversity have been controversial for over a century. Using a spatially explicit approach that incorporates not only origination and extinction but immigration, a global analysis of genera and subgenera of marine bivalves over the past 11 million years supports an "out of the tropics" model, in which taxa preferentially originate in the tropics and expand toward the poles without losing their tropical presence. The tropics are thus both a crad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

66
795
10
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 758 publications
(910 citation statements)
references
References 60 publications
66
795
10
5
Order By: Relevance
“…Our population size hypothesis would therefore predict, all else being equal, higher diversity. Further, as climate periodically causes bottlenecks at higher latitudes, this would dramatically lower the effective population sizes at high latitudes, reducing the potential for diversification ( Jablonski et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our population size hypothesis would therefore predict, all else being equal, higher diversity. Further, as climate periodically causes bottlenecks at higher latitudes, this would dramatically lower the effective population sizes at high latitudes, reducing the potential for diversification ( Jablonski et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…B IODIVERSITY varies widely across the planet, along gradients of temperature and productivity (Mittelbach et al 2001;Willig et al 2003;Hillebrand 2004;Pennisi 2005;Suding et al 2005;Jablonski et al 2006). The near-infinite complexity and variability of natural ecosystems has, perhaps, slowed our ability to both characterize patterns and elucidate mechanisms underlying the origin and maintenance of this biodiversity.…”
mentioning
confidence: 99%
“…Variation in the productivity, heterogeneity and stability of the environment may also be important for species richness. A latitudinal gradient of increasing biodiversity from the poles to the equator has been noted for many organisms (see Jablonski et al, 2006), including mosquito species (Foley et al, 2007). The underlying mechanism for this phenomenon may vary depending on the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Allen and Gillooly (2006) showed that for fossil ocean plankton, species richness and speciation rates both peak near the equator even after controlling for sampling effort and habitat area. Jablonski et al (2006) showed that for genera and subgenera of marine bivalves, taxa have preferentially originated in the tropics and expanded toward the poles without losing their tropical presence. Weir and Schlüter (2007), however, found that for birds and mammals faster speciation at higher latitudes contributes to the latitudinal diversity gradient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation